Dendrobium liquor eliminates free radicals and suppresses cellular proteins expression disorder to protect cells from oxidant damage. Issue 12 (6th October 2020) - Zhang, Xueqin; Zhao, Ruoxi; Zheng, Shigang; Chun, Ze; Hu, Yadong
Abstract: Dendrobium liquor obtained by soaking Dendrobium in Chinese liquor is considered as a health drink in China. Here, we found the pretreatment of extract of Dendrobium nobile Lindl. liquor (DNLE) attenuated the oxidative damage to cells caused by H2 O2, while the abilities of DNLE of eliminating extracellular free radicals and promoting the activities of intracellular antioxidant enzymes were observed. Quantitative proteomics identified 375 differentially expressed proteins caused by H2 O2 treatment in 293T cells. However, only 12 differentially expressed proteins were found in DNLE‐pretreated cells which under the same oxidative damage. This suggested that the pretreatment of DNLE could suppress the disorder of protein expressions caused by oxidative stress which could induce cell death. Besides, DNLE was helpful for avoiding the unfolded protein response (UPR) and cell cycle disorder caused by oxidative stress. Taken together, these results demonstrated that Dendrobium liquor could be a healthy herbal drink with antioxidant function. Practical applications: Dendrobium is used as an edible herb and a tonic food in traditional Chinese medicine. Dendrobium liquor obtained by soaking Dendrobium with Chinese liquor is also regarded as a nourishing health drink. However, there is rare research data on biological activity of Dendrobium liquor. Our current results demonstrated that the extract of Dendrobium nobile Lindl. liquor (DNLE) possessed the ability of eliminating free radicals in/out the human cells. More importantly, DNLE could help cells to resist the interference on cell life activities caused by oxidative stress. Since many evidences suggested that oxidative stress is linked to human disease and aging, and chemical antioxidant has some side effects on health, Dendrobium liquor can serve as a natural health drink with antioxidant function. Furthermore, the active ingredients in DNLE also possess the potential to be developed as natural antioxidant additive in food and cosmetics. Abstract : Dendrobium liquor eliminates extracellular free radicals and promotes the activities of intracellular antioxidant enzymes. Dendrobium liquor is helpful for avoiding unfolded protein response and cell cycle disorder caused by oxidative stress. Dendrobium liquor suppresses the disorder of cellular proteins expression caused by oxidant damage to increase the cell viability.